Disrupted Service Delivery? The Impact of Conflict on Antenatal Care Quality in Kenya - Chukwuma, Adanna; Wong, Kerry L. M.; Ekhator-Mobayode, Uche Eseosa (Frontiers in Global Women's Health, 2021)
Introduction: African countries facing conflict have higher levels of maternal mortality. Understanding the gaps in the utilization of high-quality maternal health care is essential to improving maternal survival in these states. Few studies have estimated the impact of conflict on the quality of health care. In this study, we estimated the impact of conflict on the quality of health care in Kenya, a country with multiple overlapping conflicts and significant disparities in maternal survival. Materials and Methods: We drew on data on the observed quality of 553 antenatal care (ANC) visits between January and April 2010. Process quality was measured as the percentage of elements of client–provider interactions performed in these visits. For structural quality, we measured the percentage of required components of equipment and infrastructure and the management and supervision in the facility on the day of the visit. We spatially linked the analytical sample to conflict events from January to April 2010. We modeled the quality of ANC as a function of exposure to conflict using spatial difference-in-difference models. Results: ANC visits that occurred in facilities within 10,000 m of any conflict event in a high-conflict month received 18–21 percentage points fewer components of process quality on average and had a mean management and supervision score that was 12.8–13.5 percentage points higher. There was no significant difference in the mean equipment and infrastructure score at the 5% level. The positive impact of conflict exposure on the quality of management and supervision was driven by rural facilities. The quality of management and supervision and equipment and infrastructure did not modify the impact of conflict on process quality. Discussion: Our study demonstrates the importance of designing maternal health policy based on the context-specific evidence on the mechanisms through which conflict affects health care. In Kenya, deterioration of equipment and infrastructure does not appear to be the main mechanism through which conflict has affected ANC quality. Further research should focus on better understanding the determinants of the gaps in process quality in conflict-affected settings, including provider motivation, competence, and incentives.